2023
DOI: 10.1021/acs.est.3c03181
|View full text |Cite
|
Sign up to set email alerts
|

Waterborne Tebuconazole Exposure Induces Male-Biased Sex Differentiation in Zebrafish (Danio rerio) Larvae via Aromatase Inhibition

Kun Qiao,
Zhuoying Liang,
Aoxue Wang
et al.

Abstract: Tebuconazole is a widely used fungicide for various crops that targets sterol 14-α-demethylase (CYP51) in fungi. However, attention has shifted to aromatase (CYP19) due to limited research indicating its reproductive impact on aquatic organisms. Herein, zebrafish were exposed to 0.5 mg/L tebuconazole at different developmental stages. The proportion of males increased significantly after long-term exposure during the sex differentiation phase (0−60, 5−60, and 19−60 days postfertilization (dpf)). Testosterone l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…Interestingly, upregulation of ER genes did not exhibit stereoselectivity between enantiomers (Figure A). The pathogenesis of reproductive disorders is complex and involves the modulation of multiple factors. , Previous studies have found that compared with R-(−)-MFZ, S-(+)-MFZ more severely downregulates biological processes related to ATP synthesis and metabolism, resulting in more severe mitochondrial electron flow disturbance and impaired energy supply in E. fetida .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, upregulation of ER genes did not exhibit stereoselectivity between enantiomers (Figure A). The pathogenesis of reproductive disorders is complex and involves the modulation of multiple factors. , Previous studies have found that compared with R-(−)-MFZ, S-(+)-MFZ more severely downregulates biological processes related to ATP synthesis and metabolism, resulting in more severe mitochondrial electron flow disturbance and impaired energy supply in E. fetida .…”
Section: Resultsmentioning
confidence: 99%